(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Risk classification is a clinical and organizational strategy to minimize risks and harm arising from divergences generated by access to care in health services. The technologies available for the internal audit process may generate evidence capable of ensuring the improvement/readaptation of the technologies already used in this process. Objective: To identify the technologies available for the internal audit process in risk classification. Methods: Integrative review, whose search took place during the month of May 2020, in the Latin American and Caribbean Literature in Health Sciences (LILACS), Library of Medicine National/PubMed, Cochrane Library and Specialized Bibliographic Databases in the Nursing Area (BDENF). The sample consisted of six articles. Results: Six articles were identified that portrayed the following technologies, such as the nursing triage sheet and clinical record forms; the audit protocol with feedback and the presence of facilitators; a Consensus approach and formal guidelines; consensus approach and formal guidelines; pre and post test screening; clinical audit design based on five key areas and assessed against 12 criteria: arrival and triage, documentation, policy compliance, communication, and triage staff; and standard instrument, audit of medical records and interviews. Conclusion: There are weaknesses in relation to the screening method used in institutional protocols, as well as their absence. There are few studies developed on the theme and need for recycling of health professionals involved.